Strategi Pemanfaatan Key Opinion Leader (KOL) sebagai Media Promosi Digital Jagat Satwa Nusantara - Clara Callista Ohello; Sari Ekowati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The utilization of social media has encouraged companies to use Key Opinion Leaders (KOLs) as one of their digital promotional strategies to increase brand awareness. Jagat Satwa Nusantara, as an educational tourism destination focused on wildlife conservation, has also implemented this strategy through collaborations with KOLs on social media. This study aims to analyze the strategy of utilizing Key Opinion Leaders (KOLs) as a digital promotional medium for Jagat Satwa Nusantara and its impact on brand awareness. This research uses a descriptive method with a qualitative approach. Data collection techniques were conducted through in-depth interviews, observation, documentation, and literature study. The research informants consisted of the Marketing Communication Supervisor, the KOL Specialist of Jagat Satwa Nusantara, and one KOL who had previously collaborated with the company.The research analysis applies Tuti’s theory of KOL characteristics, which includes familiarity, trustworthiness, and expertiseness, as well as Kotler and Armstrong’s theory of digital promotional media, which covers advertising, sales promotion, personal selling, direct and digital marketing, and public relations.The results of the study show that Jagat Satwa Nusantara selects KOLs based on niche relevance, audience characteristics, content performance, and engagement rate. The utilization of KOLs is most dominantly applied in the elements of advertising and public relations, supported by sales promotion and direct and digital marketing. Collaboration with KOLs has successfully expanded information reach, increased audience interaction, and strengthened the brand awareness of Jagat Satwa Nusantara, as supported by the high number of views, reach, and engagement on promotional content on Instagram.